A bio-convective investigation for flow of Casson nanofluid with activation energy applications. (March 2022) - Haq, Fazal; Saleem, Muzher; Khan, M Ijaz; Khan, Sami Ullah; Jameel, Mohammed; Sun, Tian-Chuan
Here theoretical analysis of heat, mass and motile microorganisms transfer rates in Casson fluid flow over stretched permeable surface of cylinder is studied. Investigated is carried out in the presence of suspended nanoparticles and self-propelled gyrotactic microorganisms. The effects of buoyancy forces, magnetic field and thermal radiation are considered. The nanoparticles with suitable suspension are stabilized through mutual effects of buoyancy forces and bioconvection. Furthermore, activation energy and Darcy- Forchheimer effects on bio nanofluid flow are accounted. The constitutive theories are executed to develop the model formulation. The obtained model is made dimensionless trough appropriate transformations. The dimensionless flow model is tackled by built-in algorithm of shooting technique. Impact of flow controlling constraints parameters is physically elaborated by making graphical illustrations. The outcomes based on numerical data against essential engineering formulations like surface drag force, Nusselt, density and Sherwood numbers are tabulated. Main outcomes are successfully summarized in terms of closing remarks.